PENYULUHAN COVID-19 DAN VAKSINASI COVID-19 DI LINGKUNGAN TELLULELANGE MALLAWA KECAMATAN MALLUSETASI KABUPATEN BARRU: Covid-19 Explanation And Covid-19 Vaccination In The Tellulelange Environment Mallawa, Mallusetasi District, Barru Regency - Sukirawati; Afred Rosselfed; Muhammad Fadli Alfafa; Nirwana Ibrahim; Agust Dwi Djajanti (Akademi Farmasi Yamasi Makassar, 2022)
WHO declared Covid-19 a Global Health Emergency on January 30, 2020. So this extension is one of the efforts to change people's mindset about covid-19 and provide education for prevention. The method of devotion that we do with how to explain what is meant by health protocols and the importance of covid-19 vaccination in the community and coupled with the distribution of health protocol leaflets, handsenitazers and masks. This activity was attended by 2 AKFAR Yamasi lecturers, 1 lecturer of Sandi Karsa Polytechnic and 2 students of AKFAR Yamasi Makassar and Sandi Karsa Polytechnic makassar as well as the community of Mallusetasi District of Barru Regency. Keywords : Counseling, health protocols, covid-19 vaccination